Evaluation of cephalosporins utilization and compliance with reference to the hospital antibiotic policy of an Indian tertiary care hospital - John, Shinu Mary; Panda, Bijoy Kumar; Bhosle, Deepak Govind; Soman, Nikki (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Emergence of bacterial resistance in hospital settings due to the liberal use of antibiotics which led to an altered impact on its therapeutic efficacy and outcome, thereby increasing the treatment costs in patients. In this regard the study aims to evaluate the cephalosporins utilization and compliance to the hospital antibiotic policy in general medicine ward. Methods: A prospective observational study was carried out over an eleven-month period in patients prescribed with cephalosporins. Clinical data of inpatients were collected and evaluated by using World Health Organization (WHO) core prescribing indicators and defined daily dose per 100 bed-days. The comparison between the cephalosporins prescribed in the chart records to the recommendations mentioned in the institutional antibiotic policy v.2.0, help to determine the deviations in their usage pattern. Results: A total of 370 patients were enrolled in the study, of which 54.6% were females. Cephalosporins were empirically prescribed in 240 (64.9%) cases. The average number of total antibiotics and cephalosporins per encounter was 1.6 and 1 respectively. Among the total antibiotics, 63.7% were cephalosporins. Third generation cephalosporins (98.4%) were commonly prescribed, with ceftriaxone (93%) in parenteral form for respiratory tract infections (31.9%). Total parenteral antibiotics prescribed were found to be 68.8% of which 88.6% were cephalosporins. Utilization pattern of cephalosporins amounted to be 4.95 DDD/100 bed-days. Overall compliance was achieved in 191 (51.6%) prescriptions. Conclusions: The rate of prescribing of cephalosporins was marginally high. There was a low rate of compliance towards policy which reflects the urgent need for repetitive intervention to comply antibiotic policy.